Integrating single nuclei and bulk RNA sequencing in rice shoot apical meristems uncovers candidate early floral transition gene networks - Daniele Traversa; Giulio Vicentini; Paolo Korwin Krukowski; Lucio Conti; Matteo Chiara; Vittoria Brambilla (Plant Reproduction, 2025)

Clinical efficacy of different monoclonal antibody regimens among non-hospitalised patients with mild to moderate COVID-19 at high risk for disease progression: a prospective cohort study - Alessia Savoldi; Matteo Morra; Pasquale De Nardo; Anna Maria Cattelan; Massimo Mirandola; Vinicio Manfrin; Piergiorgio Scotton; Maria Teresa Giordani; Lucio Brollo; Sandro Panese; Massimiliano Lanzafame; Giovanna Scroccaro; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
This study aimed to compare the clinical progression of COVID-19 in high-risk outpatients treated with the monoclonal antibodies (mAb) bamlanivimab, bamlanivimab-etesevimab and casirivimab-imdevimab. This is an observational, multi-centre, prospective study conducted from 18 March to 15 July 2021 in eight Italian tertiary-care hospitals including mild-to-moderate COVID-19 outpatients receiving bamlanivimab (700 mg), bamlanivimab-etesevimab (700–1400 mg) or casirivimab-imdevimab (1200–1200 mg). All patients were at high risk of COVID-19 progression according to Italian Medicines Agency definitions. In a patient subgroup, SARS-CoV-2 variant and anti-SARS-CoV-2 serology were analysed at baseline. Factors associated with 28-day all-cause hospitalisation were identified using multivariable multilevel logistic regression (MMLR) and summarised with adjusted odds ratio (aOR) and 95% confidence interval (CI). A total of 635 outpatients received mAb: 161 (25.4%) bamlanivimab, 396 (62.4%) bamlanivimab-etesevimab and 78 (12.2%) casirivimab-imdevimab. Ninety-five (15%) patients received full or partial SARS-CoV-2 vaccination. The B.1.1.7 (Alpha) variant was detected in 99% of patients. Baseline serology showed no significant differences among the three mAb regimen groups. Twenty-eight-day all-cause hospitalisation was 11.3%, with a significantly higher proportion ( p 0.001) in the bamlanivimab group (18.6%), compared to the bamlanivimab-etesevimab (10.1%) and casirivimab-imdevimab (2.6%) groups. On MMLR, aORs for 28-day all-cause hospitalisation were significantly lower in patients receiving bamlanivimab-etesevimab (aOR 0.51, 95% CI 0.30–0.88 p 0.015) and casirivimab-imdevimab (aOR 0.14, 95% CI 0.03–0.61, p 0.009) compared to those receiving bamlanivimab. No patients with a history of vaccination were hospitalised. The study suggests differences in clinical outcomes among the first available mAb regimens for treating high-risk COVID-19 outpatients. Randomised trials are needed to compare efficacy of mAb combination regimens in high-risk populations and according to circulating variants.

SUMO proteases OTS1 and 2 control filament elongation through a DELLA-dependent mechanism - Alberto Campanaro; Raffaella Battaglia; Massimo Galbiati; Ari Sadanandom; Chiara Tonelli; Lucio Conti (Plant Reproduction, 2016)